ANALISIS MATERI AJAR BUKU TEKS â€œAYO MEMAHAMI BAHASA ARAB UNTUK MTS KELAS IXâ€ KARYA HASAN SAEFULLOH DITINJAU DARI TEORI MACKEY - Mustangin Sultoni; Moch. Hasyim Fanirin; Dewi Utami (Al-mujahidah, 2023)
This thesis examines the suitability of the teaching material of the textbook "Let's Understand Arabic for MTs Class IX" by Hasan Saefulloh in terms of the theory of Mackey. The background of the problem in this research is that many Arabic text books in several schools and Islamic boarding schools have not been adapted to the learning process of Indonesians. The purpose of this study was to determine the suitability of the teaching material for the textbook "Let's Understand Arabic for MTs Class IX" by Hasan Saefulloh in terms of the theory of William Francis Mackey. This research method uses a qualitative approach and the type of research used is library research. The data collection technique in this study is the documentation method. The data analysis technique in this study used content analysis. The results showed that the textbook "Let's Understand Arabic for Class IX MTs" by Hasan Saefulloh met the selection well because of the objectives of a language learning program, the level of proficiency of students, and the length of a program. Good gradations because they are presented with rules from easy to difficult rules. The presentation is good because the start page is equipped with instructions for using the book for teachers, and each chapter is very well supported with adequate pictorials. Repetition is good because at the end of each chapter there are lots of practice questions and are equipped with examples of Final Semester Examination questions, both Odd and Even semesters.